What are the barriers and enablers that people with a lower limb amputation experience when walking in the community?. Issue 24 (19th November 2020) - Batten, Heather; Lamont, Robyn; Kuys, Suzanne; McPhail, Steven; Mandrusiak, Allison
Abstract: Purpose: To explore barriers and enablers to community walking perceived by people with lower limb amputation. Materials and methods: Three focus groups ( n = 14 participants), using purposive sampling, were conducted with people with lower limb amputation who used a prosthesis to walk in the community. Three investigators analyzed transcripts using thematic content analysis. Results: Themes aligned with the International Classification of Functioning, Disability and Health domains. Barriers related to body function and structure included prosthetic function, residual limb integrity, phantom limb pain and other medical issues, with optimal prosthetic function and adequate fitness identified as enablers. Personal barriers included challenges adjusting to change, whereas personal enablers included being able to adjust to change, having a positive attitude, goal setting and a purpose for community walking. Environmental barriers included physical (e.g., terrain, crowds, climate) and social (e.g., unwanted attention and finances). Environmental enablers included aids, transport, preparation, social support and finances. Community walking was essential to participation in work, leisure, social activities and family roles. Conclusion: Walking in the community for people with a lower limb amputation presents many barriers, but enablers have also been identified. Targeted assessments and interventions, and appropriate environmental planning may assist in minimizing barriers to community walking. Implications for rehabilitation: Although rehabilitation for people with lower limb amputation should continue to optimise body function and structure (such as strength, fitness, pain and prosthetic function) to help prepare individuals for walking in the community, personal and environmental factors should also be addressed. Optimising an individual's personal enablers may facilitate community walking; this may include strategies to assist with adjusting to change, setting goals, instilling a positive attitude towards walking, and seeing a purpose for walking in the community. Enhancing environmental (physical and social) enablers and minimising environmental barriers to walking in the community may be possible through environmental planning (e.g. infrastructure such as lifts), social awareness and education.